A Collaborative Program for the 2020 Great Solar Eclipse in Argentina - Basset, Ana Maria; Ramos, S.; Olavegogeascoechea, Mara Adriana; Rucci, M.; Camino, Néstor Eduardo; Paolantonio, S.; Corti, M.; Garcia, Beatriz Elena (International Astronomical Union, 2021)
Fil: Basset, Ana Maria. Universidad Nacional del Comahue. Facultad de Ingeniería. Departamento de Física; Argentina